Dietary fiber, carbohydrate quality and quantity, and mortality risk of individuals with diabetes mellitus. - Burger, K; Beulens, J; van der Schouw, Y; Sluijs, I; Spijkerman, A; Sluik, D; Boeing, H; Kaaks, R; Teucher, B; Dethlefsen, C; Overvad, K; Tjønneland, A; et al. (2012)
BACKGROUND: Dietary fiber, carbohydrate quality and quantity are associated with mortality risk in the general population. Whether this is also the case among diabetes patients is unknown. OBJECTIVE: To assess the associations of dietary fiber, glycemic load, glycemic index, carbohydrate, sugar, and starch intake with mortality risk in individuals with diabetes. METHODS: This study was a prospective cohort study among 6,192 individuals with confirmed diabetes mellitus (mean age of 57.4 years, and median diabetes duration of 4.4 years at baseline) from the European Prospective Investigation into Cancer and Nutrition (EPIC). Dietary intake was assessed at baseline (1992-2000) with validated dietary questionnaires. Cox proportional hazards analysis was performed to estimate hazard ratios (HRs) for all-cause and cardiovascular mortality, while adjusting for CVD-related, diabetes-related, and nutritional factors. RESULTS: During a median follow-up of 9.2 y, 791 deaths were recorded, 306 due to CVD. Dietary fiber was inversely associated with all-cause mortality risk (adjusted HR per SD increase, 0.83 [95% CI, 0.75-0.91]) and CVD mortality risk (0.76[0.64-0.89]). No significant associations were observed for glycemic load, glycemic index, carbohydrate, sugar, or starch. Glycemic load (1.42[1.07-1.88]), carbohydrate (1.67[1.18-2.37]) and sugar intake (1.53[1.12-2.09]) were associated with an increased total mortality risk among normal weight individuals (BMI≤25 kg/m(2); 22% of study population) but not among overweight individuals (P interaction≤0.04). These associations became stronger after exclusion of energy misreporters. CONCLUSIONS: High fiber intake was associated with a decreased mortality risk. High glycemic load, carbohydrate and sugar intake were associated with an increased mortality risk in normal weight individuals with diabetes.